Lactobacillus rhamnosus R0011 Treatment Enhanced Efficacy of Capecitabine against Colon Cancer in Male Balb/c Mice. (30th June 2022) - Rahimpour, Milad; Ashabi, Ghorbangol; Rahimi, Ahmad Mustafa; Halimi, Shahnaz; Panahi, Mahshid; Alemrajabi, Mahdi; Nabavizadeh, Fatemeh
Abstract: The microbiome of the intestinal system is well-known as a modulatory factor. Having a balanced status of microbiota could help to prevent diseases, especially cancers related to the gastrointestinal system. We investigated the effects of Lactobacillus rhamnosus ( Lr ) and capecitabine on tumor size and physiologic features, such as bodyweight, liver enzymes, and blood profile, in a subcutaneously induced cancer model using CT-26 murine colon carcinoma cells. We divided 48 male Balb/c inbred mice into six groups. Lr had been orally pre-inoculated to the mice for 14 day consecutively. CT-26 cells were implanted subcutaneously into the mice's flank. Following the injection of cancer cells, Lr was inoculated to the mice three times per week for four weeks. Capecitabine was inoculated in the third week after the induction of cancer. The tumor size was significantly decreased in treated groups in comparison to the cancer group (1174.5 ± 63.8, 1119.2 ± 86.3, and 985.6 ± 48 mm 3 vs. 1674.2 ± 66 mm 3, P < 0.0001). Data showed that Lr and capecitabine enhanced Bax/Bcl-2 ratio and caspase-3 level compared to cancer group ( p < 0.0001). White blood cells (WBCs) were significantly decreased in the capecitabine group compared to probiotic group ( P < 0.05). Measurement of bodyweight, liver enzymes, and interleukin-6 (IL-6) level showed that Lr, in addition to preventive and therapeutic effects, might have protective effects against chemotherapy side effects. Preventing WBCs' reduction, protecting mice from losing weight, induction of apoptosis, and enhancing the serum level of IL-6 indicated that Lr might be associated with better management of colorectal cancer and chemotherapy side effects.